Diseño de un modelo de gestión para la compañía de transporte turístico RIOEMPRES TOURS S.A - Romero Bustamante, Marcela Verónica (2016)
El presente estudio tiene como objetivo el diseño de un modelo de gestión bajo el concepto del Balanced Scorecard para la compañía de transporte turístico Rioempres Tours en la ciudad de Riobamba, que permita administrar, controlar y lograr un servicio más eficiente e innovador; la misma que está estructurada por cuatro capítulos:En el capítulo 1, se presenta el marco teórico, en donde se muestran las definiciones necesarias para la comprensión del tema, a medida que se desarrolla el presente trabajo.This study has the purpose to design a management model under the concept of Balanced Scorecard for the carrier company Riompres Tours in the city of Riobamba, which manages control and achieve more efficient and innovate service the same it is structure by four chapters: • Chapter 1: the theoretical framework, which presented the necessary definitions to understanding the subject, this work develops. • Chapter 2: this show the situational analysis that allows to know the philosophy of the carrier company RIOEMPRES TOURS S.A that is to say the identity and the purposes to being of the company that includes vision mission and strategies that is following it.